Proactive Study on the Toxicity of Ficus benghalensis Leaf Extract in Rat Models Preceding the Exploration of Therapeutic Benefits - Kalyan Acharjya, Sushila Arya, Neetha SS (Revista Electronica de Veterinaria, 2024)
Traditional Indian medicine has made extensive use of the Banyan tree, scientifically called Ficus benghalensisto cure several diseases. For diarrhea, Charka recommended soaking the Nyagrodha (Ficus benghalensis) leaf buds in water. The leaves of the Ficus benghalensis tree can offer analgesic, antipyretic, and anti-ulcerogenic properties, according to recent studies. Finding the oral toxicity profile of a methanol extract of the Ficus benghalensis plant's leaves in Wister albino rats was the aim of the study.  Ficus benghalensis leaf extract (FbLEx) was administered orally to the rats once, at 100, 500, 1000, 2000, 4000, and 5000 mg/kg.  Over a span of fourteen days, we monitored overall behavior and harmful symptoms.  The acute toxicity of FbLEX, animals were given a diluted solution of the extract in methanol. At the end of the fourteen days of therapy, there were no reports of mortality or behavioural abnormalities. Furthermore, no negative effects were seen throughout the clinical testing, indicating that the extract was administered orally at a dosage exceeding 5,000 mg/kg body weight without causing any damage. However, the histology study found tiny alterations in the heart and kidneys. In conclusion, more investigations on the repeated dose toxicity of Ficus benghalensis leaves are needed to confirm their long-term safety. However, according to toxicological tests, the methanol extract of the plant was shown to be quite safe when taken orally.